Patient/client safety structures and processes in home care: A cross-sectional online survey - Heli Vaartio-Rajalin; Auvo Rauhala; Jaana Kalliokoski; Tuija S Ikonen (Patient Safety and Quality Improvement Journal, 2022)
Introduction:The complexity of home care is demanding in terms of patient/client safety. The aim of this study was to explore patient/client safety structures and processes within organizations providing home care during the reform of home care and the supervision of patient/client safety in Finland. Materials and Methods: A cross-sectional exploratory online survey for persons responsible for safety strategies at home care organizations (home nursing, hospital-at-home, home services). Results: The majority of organizations (89%) had a patient/client safety plan, which included central safety strategies and responsibilities. However, the authority responsible for the various dimensions of patient/client safety varied. Regarding responsibility for the supervision of care personnel’s surveys and reports of the hazardous and adverse events, a significant difference was seen between organizations providing both home nursing and social services versus only social services (94% vs. 49%, [CI 34%-64%] p <.001). Patient and client centered measures varied from patient/client service and care consultation processes (81%) to patient/client safety observation rounds (24%). Care personnel were seen to have a function as Everyday safety “watchdogs” or “Safety whistleblowers”, and employ a broad range of preventive and reactive methods for patient/client safety. Conclusion:Most organizations were seen to have well-established, organizational patient/client safety structures and processes. The methods used to identify, prevent, minimize, and report safety problems were mostly proactive, indicating an active, analytic, and learning safety culture. Current challenges included involving service users and new employees in safety processes to create a truly comprehensive and sustainable safety culture.